FOREIGN BODY INHALATION - SITE OF IMPACTION AND EFFICACY OF RIGID BRONCHOSCOPY - Asif, Muhammad; Shah, Shahid Ali; Khan, Farida; Ghani, Rehman (Journal of Ayub Medical College Abbottabad, 2007)
Background: Foreign body inhalation is a relatively commonly encountered emergency in otolaryngology. Foreign body can get lodged at any site from the supraglottis to the terminal bronchioles. Rigid bronchoscopy is one of the well established methods of removing inhaled foreign body with fewer complications. Methods: This prospective study was conducted in the Department of ENT, Head & Neck Surgery, Ayub Teaching Hospital, Abbottabad, from January 2003 to June 2005. The total number of patients was eighty one. Patients in whom a foreign body was retrieved, were included in the study. Results: Foreign body was found in the right main bronchus in sixty patients (74.1%), left main bronchus in seventeen patients (21%), terminal bronchioles in two patients (2.5%) and one patient (1.2%) each in trachea and laryngeal inlet. Foreign body was successfully removed in seventy-nine patients (97.5%). Nineteen patients (23.5%) had postoperative airway edema, one (1.2%) had trauma to the false cord and laceration of the posterior pharyngeal wall. Conclusion: It was concluded that the right main bronchus is the most common site of impaction of inhaled foreign body. Rigid bronchoscopy is very effective procedure for inhaled foreign body removal with fewer complications. Keywords: Foreign body; Bronchoscopy; Trachea